Outcome of Difficult Pelvis Surgeries done by Gynecologist versus General Surgeons - Muhammad Afzal, Munawer Latif Memon, Shahid Hussain Mirani, Fozia Unar (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the outcomes of difficult pelvis surgeries done by gynecologist versus general surgeons. Study Design: Retrospective study Place and Duration of Study: Department of Surgery, CMH Kharian Medical College, Kharian, Department of Surgery, Wah Medical College POF Hospital, Wah Cantt and Ghulam Muhammad Mahar Medical College, Teaching Hospital, Sukkur from 1st August 2015 to 31st July 2018. Methodology: Fifty professionals (who conducted 500 pelvic surgeries) were included either from the surgery or obstetrics gynecology departments. The study was initiated post-consent of each participant. Surgeons National Surgical Quality Improvement Program (NSQIP) data base software was applied for designing the questionnaire. The NSQIP database collects information from 10 perioperative-variables, as well as preoperative-comorbidities, parity, previous history of pelvic surgery, ureteral obstruction and vesico-vaginal fistula, intraoperative-variables, as well as 30-day mortality and morbidity outcomes including the rate of reoperation and re-admission. Other information regarding ASA classification and malignancy were also collected. Result: There were 341 procedures performed by surgeons while 159 procedures were conducted obstetrics gynecologists’ surgeons. The mean age of the patients was 62.5±11.5 years. The ASA classification presented higher number of surgeries in class 1 and 2 of the ASA class. The apical procedures as Sacrospinous and Sacrocolpopexy were performed highest by obstetrics gynecologists. The 30 days postoperative complication rate was increased significantly in the obstetrics gynecologists group than the surgeons. Conclusion: Prolapse surgery completed by a surgeon is linked with lower odds of 30-day postoperative-complications than the one performed by the obstetrician-gynecologist. Keywords: Outcome, Pelvis surgery, Prolapse surgery, Complication